2020
DOI: 10.2196/16494
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-Based, Peer-Delivered Messaging Intervention for HIV Testing and Condom Use Among Men Who Have Sex With Men in India (CHALO!): Pilot Randomized Comparative Trial

Abstract: Background Leveraging internet-based communication tools (eg, messaging apps, SMS text messaging, and email) may be an effective avenue for delivery of HIV prevention messages to men who have sex with men (MSM) in India, but there are limited models for such internet-based interventions. Objective The CHALO! pilot was an online educational and behavioral intervention aimed to determine the feasibility, acceptability, and preliminary impact of a peer-del… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 55 publications
0
56
0
2
Order By: Relevance
“…The recall period for these studies varied, with one study reporting lifetime HIV testing history and the remaining studies using recall periods that ranged from 3 months to 3 years. A total of 10 studies used an RCT design [ 46 - 49 , 51 , 54 - 58 ]. The specific study design used by the remaining 3 studies was a prospective cross-sectional study with nonequivalent control group [ 50 ], a prospective single-group cross-sectional study [ 52 ], and a prospective cross-sectional matched-pair randomized trial design [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The recall period for these studies varied, with one study reporting lifetime HIV testing history and the remaining studies using recall periods that ranged from 3 months to 3 years. A total of 10 studies used an RCT design [ 46 - 49 , 51 , 54 - 58 ]. The specific study design used by the remaining 3 studies was a prospective cross-sectional study with nonequivalent control group [ 50 ], a prospective single-group cross-sectional study [ 52 ], and a prospective cross-sectional matched-pair randomized trial design [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of individual-level randomization and nonequivalence of control groups, we calculated relative risk for these 3 studies using reported HIV testing uptake at preintervention baseline and postintervention endpoints in the intervention arm only. One RCT described two intervention arms and did not present disaggregated findings; therefore, this study was treated as a single cohort, and relative risk was calculated based on HIV testing uptake at baseline and endpoint [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations